Survey of medical oncologists and trainee practice on venous thromboembolism prophylaxis and treatment in solid cancers. Issue 1 (24th January 2023) - Yeung, James; Tjokrowidjaja, Angelina; Lewis, Craig; Lynch, Jodi
Abstract: Venous thromboembolism (VTE) has a significant adverse impact on the outcomes of patients with active solid malignancies. Prophylaxis is indicated for cancer‐associated VTE (CA‐VTE) using the Khorana score for risk stratification. We surveyed medical oncology fellows and trainees regarding their practice in CA‐VTE. Regarding treatment of CA‐VTE, practice was consistent with guidelines. However, regarding prophylaxis for CA‐VTE, there was a high degree of uncertainty, which highlights the need for ongoing education.